MEMBANGUN KOMUNIKASI INTERPERSONAL ORANG TUA DENGAN ANAK DALAM KELUARGA - Fensi, Fabianus (Universitas Bunda Mulia, 2017)
The communication model in the family is part of the interpersonal communication. Here the role of parents can be called as the main communicator in the delivery of communication messages. To achieve the effectiveness of a parent communication certainly has its own way of delivering messages to their children, especially when children face certain problems in their social life. As an effective message delivery standard, this activity suggests three possible patterns of communication skills, including: listening communication; Open communication; and honest communication. Listening communication is a parent-to-child interpersonal communication model, or a form of communication involved, especially in responding to the psychological needs of the child. Open communication is a communication that enables messengers and message recipients to understand what they want to achieve in an ongoing communication. Parents as messengers and children as recipients of the message occupy the same position in the exchange of communication messages they are building. While honest communication is a communication model that is delivered with the aim of fostering self-esteem of children. These three models of communication, apart from being the most important way to find solutions to problems faced by children, as well as a way to counter the tendency of self-egoism of parents. With these communication patterns parents are able to absorb what children expect. And, in this way, children feel understood and appreciated by their parents.Keywords: Interpersonal Communication, Listening, Open, Honest.